Anderson's atlas of hematology - Anderson Young, Shauna Christine, 1945-; Poulsen, Keila (Burlington : Jones & Bartlett Learning, LLC, an Ascend Learning Company, 2021)
"Anderson's Atlas of Hematology is the most comprehensive atlas for the laboratory technologist and laboratory scientist as well as those in training. This atlas equips students with visual examples of the concepts covered in their programs. With its four-color illustrations and clear descriptions, this atlas enables you to describe and identify all stages in the development of blood cells. Moreover, it provides an illustrated guide to a broad range of hematologic disorders. This multifaceted text can be used as a quick reference, study guide, or atlas"--
Red Blood Cells -- White Blood Cells -- Megakaryocytes -- Comparison of Cells -- Cellularity -- Cells of the Reticuloendothelial System -- Nonhematopoietic Cells -- Cytochemical Stains -- Erythrocytosis -- Anemias Due to Disordered Iron Metabolism or Heme Synthesis -- Megaloblastic Anemias -- Hypoproliferative Anemias -- Hemoglobinopathies -- Hemolytic Anemias -- Acute Blood Loss -- Anemias Associated with Systemic Disorders -- Nonmalignant Leukocyte Disorders -- French American British (FAB) Classification of Leukemia -- World Health Organization (WHO) Classification of Tumors of Hematopoietic and Lymphoid Neoplasms -- Myeloproliferative Neoplasms -- Mastocytosis -- Myelodysplastic/Myeloproliferative Neoplasms -- Myelodysplastic Syndromes -- Acute Myeloid Leukemia (AML) and Related Precursor Neoplasms -- Precursor Lymphoid Neoplasms -- Mature B-cell -- Mature T- and NK-cell Neoplasms -- Quantitative Platelet Disorders --Hematologic Disease Associated with Microorganisms -- Reticuloendothelial System Storage Disorders
Includes bibliographical references and index.
Keywords: Hematologic Diseases -- pathology; Blood Cells -- pathology; Atlas